Evaluating project achievement of ITSP implementation: a case study - Jusoh, Yusmadi Yah; Hamdan, Abdul Razak; Deraman, Aziz (2007)
Information Technology Strategic Planning (ITSP) was developed to emphasize the organization’s target for the information technology (IT). The aim was mainly to assign IT contributions towards the efficiency, effectiveness and competitiveness. The plan also comprise of associated projects to achieve the target. Previous study has concluded that most of the strategies formulated fail to be implemented. The strategy accomplishment is reflecting by the projects achievement. Therefore, measuring the implementation of ITSP is important to justify the accomplishment of the planned projects. The focus of this paper is on evaluating the projects performance of the ITSP implementation. Thus, based on the on-going research we have proposed a process for measuring the project success. The proposed performance measurement was tested on the real case study. The result is presented and described further in this paper.